Using a computer in the sports science in the Republic of Iraq (1988-2012) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study discuss (6) important uses of computer in sports science , the dates of these usage differ from year to other and interfere with each other, show who the progress in the Republic of Iraq increase , graduate students use some applications are not specialized like (AutoCAD) and  investing it in the analyzing movement in scope of sports, using part of this application solution a big problem in measuring angles and distances, graduate students use several applications such as (Dartfish) as it has been to solve many problems using this application especially those problems related to high speed camera as accumulates a large number of images in programs that do not have the ability to deal with films that use modern applications in application after another demonstrates the weakness of previous applications in solving problems later, the speed of processors and techniques screens minute made some companies are racing to receive its programs to films with extensions.In this study, a historical account of the uses of computer in the Republic of Iraq began in 1988 using a computer for the first time in Basic language and ending in the year 2012 using the computer as an intermediary for applications, and found that the computer had been used in each of  analyzing of athletic movements, take advantage of it in the field of biomechanical feedback, in the education movements by displaying movements and replay it on monitor, use computer software in the field of three-dimensional and discover dimensions of skill, used as an intermediary for some devices such as measuring the electrical activity of muscles (EMG), force platforms, finely use a computer in the field of building models